2008
DOI: 10.1007/s00109-008-0378-3
|View full text |Cite
|
Sign up to set email alerts
|

IKK-2 is required for TNF-α-induced invasion and proliferation of human mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) can contribute to tissue repair by actively migrating to sites of tissue injury. However, the cellular and molecular mechanisms of MSC recruitment are largely unknown. The nuclear factor (NF)-kappaB pathway plays a pivotal role in regulating genes that influence cell migration, cell differentiation, inflammation, and proliferation. One of the major cytokines released at sites of injury is tumor necrosis factor-alpha (TNF-alpha), which is known to be a key regulator of the NF-kappa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 52 publications
6
74
1
1
Order By: Relevance
“…14,81 Exposure to TNF-a significantly affects the in vitro protein expression, proliferation, and migration of undifferentiated human MSCs, but has not been reported to induce differentiation. 11,82 Thus, to study the effects of TNF-a on osteogenically differentiating MSCs, supplements must be added to induce MSC osteogenic differentiation. Studies of the effects of TNF-a on osteogenic differentiation have been complicated by the fact that two supplements typically used to stimulate in vitro MSC osteogenic differentiation, dexamethasone and ascorbic acid, antagonize TNF-a signaling.…”
Section: Tnf-amentioning
confidence: 99%
“…14,81 Exposure to TNF-a significantly affects the in vitro protein expression, proliferation, and migration of undifferentiated human MSCs, but has not been reported to induce differentiation. 11,82 Thus, to study the effects of TNF-a on osteogenically differentiating MSCs, supplements must be added to induce MSC osteogenic differentiation. Studies of the effects of TNF-a on osteogenic differentiation have been complicated by the fact that two supplements typically used to stimulate in vitro MSC osteogenic differentiation, dexamethasone and ascorbic acid, antagonize TNF-a signaling.…”
Section: Tnf-amentioning
confidence: 99%
“…Indeed, tissue injury seems to release soluble factors (TNF-alpha, SDF-1, etc.) capable of attracting and facilitating the homing of MSCs, which would enhance their repair/regeneration capabilities [40,41], and there are already a variety of preclinical studies and clinical trials exploring the repair/regeneration potential of MSCs in injured tissues (eg, sepsis, acute myocardial infarction, graft-versus-host disease, Crohn's disease, and acute lung injury). However, fetal intervention into uninjured fetal organs seeks to prevent diseases before the onset of irreversible damage.…”
Section: Moreno Et Almentioning
confidence: 99%
“…The facts that TNF-␣-induced IB␣ phosphorylation requires IKK␤ (Hayden and Ghosh, 2004;Böcker et al, 2008;Schmid and Birbach, 2008) and is inhibited by LYG-202 prompted us to determine the effect of LYG-202 on IKK␤ activation. Results from the IKK␤ kinase assay showed that LYG-202 obviously suppressed IKK␤ activity in a dose-dependent manner (Fig.…”
Section: Lyg-202mentioning
confidence: 99%